A randomized comparison of low dose ropivacaine programmed intermittent epidural bolus with continuous epidural infusion for labour analgesia - Riazanova, Oksana V. (Rom J Anaesth Intensive Care, 2019)
BACKGROUND: Two methods of local anaesthetic administration into the epidural space in natural delivery pain management are compared in the article. Methods compared are programmed intermittent epidural bolus (PIEB) and continuous epidural infusion (CEI). Patient-controlled epidural analgesia was provided simultaneously in all cases. METHODS: 84 primipara with average age 30.7 (27.5–34) years, and gestational age 39.1 (38.5–40) weeks planned to natural delivery were examined. PIEB and patient controlled epidural analgesia was used in the first group. Patient controlled epidural analgesia and continuous epidural infusion (CEI) of local anaesthetic was used in the second group. Ropivacaine hydrochloride 0.08% without any adjuvants was utilized as local anaesthetic. Pain assessment was conducted using VAS while motor block was assessed using the Bromage scale. RESULTS: Labor progression dynamics and condition of newborns were equally independent to the method of analgesia. However, analgesic endpoint was better and more long-lasting while using PIEB with patient controlled epidural analgesia. Moreover, a lesser amount of local anaesthetic was consumed. In the group with programmed bolus, the total volume of local anaesthetic was 59.9 (45–66) ml in comparison with 69.5 (44–92) ml in the continuous infusion group (p = 0.033). The time to first bolus requested by the puerpera was significantly longer in the programmed bolus group – 89.2 (57–108) min compared to 43.2 (35–65) minutes in the continuous infusion group (p = 0.021). CONCLUSION: Administration of low-concentrated ropivacaine solution 0.08% with no opioids using PIEB provides better and more prolonged analgesia with less local anaesthetic consumption and without any additional maternal and newborn side effects in comparison with continuous infusion.